PENDAMPINGNAN PENGAJUAN ARTIKEL ILMIAH DIJURNAL ILMIAH ONLINE BAGI MAHASISWA AKHIR STUDI - Safriyanto Dako; Safriyanto Dako; Nibras K Laya; Syukri I Gubali; Suparmin Fathan; Fahria Datau; Sri Yeni Pateda (Jambura Journal of Husbandry and Agriculture Community Serve, 2023)
The purpose of this service is to provide student assistance in submitting and publishing articles in online journals and induction of the Mendeley application. The dedication method uses the Active Participant Participation (PRA) model. Submitting articles in scientific journals generally uses 5 steps to submit (according to the rules of the intended journal and depending on the OJS application used in the journal). After logging in to scientific journals (journals using OJS 2): Click new submission (1), Submit a draft article (Uploading the submission) (2), Fill in the metadata for each Author (Enter Metadata Submission) (3), Upload Supplementary Files namely uploading data related to the contents of the article for revision, generally there are separate instructions from the journal editor (4). Confirming Submission, The inside is the final step and saving your article file can be submitted. Organizing mentoring for submitting articles in online journals, induction of Mendeley applications, and providing expertise that makes it easier for students to write scientific articlesKata Kunci: Jurnal online; Artikel Ilmiah; Aplikasi mendeley